Specific effects of background electrolytes on the kinetics of step propagation during calcite growth - Ruiz-Agudo, E.; Putnis, Christine; Wang, L.; Putnis, Andrew (2011)
The mechanisms by which background electrolytes modify the kinetics of non-equivalent step propagation during calcite growth were investigated using Atomic Force Microscopy (AFM), at constant driving force and solution stoichiometry. Our results suggest that the acute step spreading rate is controlled by kink-site nucleation and, ultimately, by the dehydration of surface sites, while the velocity of obtuse step advancement is mainly determined by hydration of calcium ions in solution. According to our results, kink nucleation at acute steps could be promoted by carbonate-assisted calcium attachment. The different sensitivity of obtuse and acute step propagation kinetics to cation and surface hydration could be the origin of the reversed geometries of calcite growth hillocks (i.e., rate of obtuse step spreading<rate of acute step spreading) observed in concentrated (ionic strength, IS=0.1) KCl and CsCl solutions. At low IS (0.02), ion-specific effects seem to be mainly associated with changes in the solvation environment of calcium ions in solution. With increasing electrolyte concentration, the stabilization of surface water by weakly paired salts appears to become increasingly important in determining step spreading rate. At high ionic strength (IS=0.1), overall calcite growth rates increased with increasing hydration of calcium in solution (i.e., decreasing ion pairing of background electrolytes for sodium-bearing salts) and with decreasing hydration of the carbonate surface site (i.e., increasing ion pairing for chloride-bearing salts). Changes in growth hillock morphology were observed in the presence of Li+, F- and SO42-, and can be interpreted as the result of the stabilization of polar surfaces due to increased ion hydration. These results increase our ability to predict crystal reactivity in natural fluids which contain significant amounts of solutes. © 2011 Elsevier Ltd.